The War and Democracy - Seton-Watson, R. W. (Robert William), 1879-1951; Greenwood, Arthur, 1880-1954; Wilson, John Dover, 1881-1969; Zimmern, Alfred, 1879-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"The War and Democracy" by R.W. Seton-Watson, J. Dover Wilson, Arthur Greenwood, and Alfred E. Zimmern is a historical account written during the early 20th century amid the devastating backdrop of World War I. The book delves into the complex interplay between war and democratic ideals, focusing on how the ongoing conflict affects societies and governance across Europe. Through careful analysis, it explores the duties and responsibilities of citizens in a democracy during times of crisis, urging readers to understand the profound implications of the war on their political and social structures. The opening of the book establishes the harrowing context of World War I, emphasizing the urgent need for citizens to grapple with their roles and responsibilities in a rapidly changing world. It reflects on the collective responsibility of the British public and highlights the perceived failure of democratic governance to engage citizens in crucial foreign policy matters. The authors outline a threefold responsibility that citizens must address: understanding their current duties, reflecting on the reasons for the war, and contemplating the future and the principles guiding a just peace. In doing so, they aim to stimulate thought and discussion among their readership about the underlying issues and causes of the war, positioning democracy not merely as a form of government but as a vital spirit that drives the well-being of society. (This is an automatically generated summary.)
Release date is 2004-01-01
Produced by Jonathan Ingram, Lazar Liveanu and PG Distributed Proofreaders
Keywords: World War, 1914-1918; Nationalism -- Europe; Europe -- Politics and government -- 1871-1918